2002
DOI: 10.1557/proc-754-cc9.4
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Deformation in the Amorphous or Partially Crystallized Zr41.2Ti13.8Cu12.5Ni10Be22.5 Bulk Metallic Glass

Abstract: The high temperature deformation of the Zr41.2Ti12.5Cu13.8Ni10Be22.5 bulk metallic glass (BMG) is studied in the supercooled liquid region. Both fully amorphous and partially crystallized states are investigated. In the studied experimental domain, the amorphous alloy exhibits a Newtonian behavior at high temperature and/or low strain rate whereas a transition to non-Newtonian behavior is observed when the temperature is decreased and/or the strain rate is increased. In the Newtonian domain, the dependency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The dispersion of nano-crystalline particles with an amorphous structure increases the elastic modulus [5], hardness [5][6][7], and tensile strength [8]. Wang et al [9] quantified the effect of crystallization on hardening in high temperature deformation of BMG. Zhang et al [10] observed that, after full crystallization of the Zr 48 Nb 8 Cu 14 Ni 12 Be 18 BMG, the material demonstrated a 40% increase in hardness, 20% increase in elastic constant, 6.7% increase in thermal expansion coefficient, and 1.6% increase in density.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of nano-crystalline particles with an amorphous structure increases the elastic modulus [5], hardness [5][6][7], and tensile strength [8]. Wang et al [9] quantified the effect of crystallization on hardening in high temperature deformation of BMG. Zhang et al [10] observed that, after full crystallization of the Zr 48 Nb 8 Cu 14 Ni 12 Be 18 BMG, the material demonstrated a 40% increase in hardness, 20% increase in elastic constant, 6.7% increase in thermal expansion coefficient, and 1.6% increase in density.…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity vs. strain-rate at different temperatures. other compositions of Zr-based bulk metallic glasses [3,19]. Q = 432, 410 and 375 kJ/mol have been obtained by compression tests for the compositions of Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 [19], Zr 55 Cu 30 Al 10 Ni 5 [3] and Zr 65 Cu 15 Al 10 Ni 10 [3], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Such composites can be made by introducing the particles ex situ prior to casting [5][6][7], or by the formation of the crystalline phase in situ. The latter can be carried out by the crystallization of the amorphous matrix or the formation of the crystalline phase during casting [8][9][10][11][12][13]. It is also possible to use liquid immiscible alloys for this purpose [12][13][14].…”
Section: Introductionmentioning
confidence: 99%